The Hubungan Lingkar Pinggang Dengan Kejadian Hiperkolesterolemia Pada Penderita Hipertensi di Puskesmas Tegal Gundil Kota Bogor: Relationship Of Waist Circumference And Hypercholesterolemia Incidence In Patient With Hypertension in Tegal Gundil Public Health Center at Bogor City - Siti Hana; Ratu Ayu Dewi Sartika (Jurnal Kesehatan Komunitas, 2019)
Hypertension and hypercholesterolemia are the causes of coronary heart disease (CHD) so that the presence of hypercholesterolemia in patients with hypertension will increase the risk of CHD. Central obesity describes the accumulation of fat in the stomach which can lead to abnormalities in the amount of lipids in the blood, when it occurs in patients with hypertension can lead to progression of the occurrence of high blood cholesterol and the risk of causing atherosclerosis and heart disease. The purpose of this study was to determine the relationship of waist circumference and other factors with the incidence of hypercholesterolemia in patients with hypertension. This research is a quantitative study through secondary data with Cross Sectional design. According to the results of multivariate tests with multiple logistic regression, there was a relationship between waist circumference, gender and age after being controlled by physical activity variables. Gender as a risk factor most associated with the incidence of hypercholesterolemia with a risk 8.5 times higher in women than men, then carried out waist circumference stratification test by sex in hypertensive patients with cases of central obesity found a significant relationship that women with central obesity have a risk of experiencing hypercholesterolemia as much as 5.5 times compared to central obesity in men with a value of p <0.05. There is a waist circumference relationship with the incidence of hypercholesterolemia in women who are central obesity more at risk of developing hypercholesterolemia than central obesity in men. Keywords: Hypercholesterolemia, waist circumference, hypertensive patients